Indicadores del proceso de tamizaje de cáncer de mama en México: un estudio de caso - Santos Uscanga-Sánchez; Gabriela Torres-Mejía; Angélica Ángeles-Llerenas; Raúl Domínguez-Malpica; Eduardo Lazcano-Ponce (Instituto Nacional de Salud Pública, 2014)
To identify, measure and compare the performance indicators of productivity, effective access and quality service for the early detection breast cancer program in Mexico. Material and methods. By means of a study case based on the 2011 Women Cancer Information System (Sicam), the indicators were measured and compared with the Mexican official standard NOM-041-SSA2-2011 and international standards. Results. The analysis showed insufficient installed capacity (37%), low coverage in screening (15%), diagnostic evaluation (16%), biopsy (44%) and treatment (57%), and very low effectiveness in confirmed cases by the total number of screening mammograms performed (0.04%). There was no information available, from Sicam, to estimate the rest of the indicators proposed. Conclusions. Efficient health information systems are required in order to monitor indicators and generate performance observatories of screening programs.